Association of unemployment and increased depressive symptoms with all-cause mortality: follow-up study of a cardiovascular prevention programme - Korhonen, Päivi E.; Kautiainen, Hannu; Rantanen, Ansa T. (OXFORD UNIV PRESS, 2025)
Unemployment has been associated with increased risk of cardiovascular disease (CVD) and all-cause mortality. However, factors behind this association remain unsettled. A primary care CVD prevention programme was conducted in two Finnish towns in 2005-07. Of the participants (n = 4450), a cohort of apparently healthy CVD risk subjects belonging to the labour force (n = 1487) was identified. Baseline depressive symptoms were assessed by Beck's Depression Inventory. Data on employment status and mortality were obtained from official statistics. The effect of employment status and depressive symptoms on all-cause mortality after a median follow-up of 15 years was estimated in models adjusted for age, sex, body mass index, non-high-density lipoprotein cholesterol, physical activity, alcohol use, current smoking, glucose metabolism, and hypertension. In comparison to employed non-depressive subjects, fully adjusted hazard ratio (HR) for all-cause mortality was 3.53 (1.90-6.57) in unemployed subjects with increased depressive symptoms, 1.26 (0.68-2.34) in unemployed non-depressive subjects, and 1.09 (0.63-1.90) in employed depressive subjects. Factors independently associated with mortality were unemployment with increased depressive symptoms [HR 3.56 (95% CI 1.92-6.61)], screen-detected diabetes [HR 2.71 (95% CI 1.59-4.63)], current smoking [HR 1.77 (95% CI 1.19-2.65)], and higher age [HR 1.10 (95% CI 1.05-1.15)]. Unemployment in itself was not associated with all-cause mortality. If unemployment was accompanied with increased depressive symptoms, risk of death was significantly elevated.